Sequencing of laser captured Z and W chromosomes of the tocantins paradoxical frog (Pseudis tocantins) provides insights on repeatome and chromosomal homology - Gatto, Kaleb Pretto [UNESP]; Timoshevskaya, Nataliya; Smith, Jeramiah J.; Lourenço, Luciana Bolsoni (Oxford University Press (OUP), 2022)
Pseudis tocantins is the only frog species of the hylid genus Pseudis that possesses highly heteromorphic sex chromosomes. Z and W chromosomes of Ps. tocantins differ in size, morphology, position of the nucleolar organizer region (NOR) and the amount and distribution of heterochromatin. A chromosomal inversion and heterochromatin amplification on the W chromosome were previously inferred to be involved in the evolution of this sex chromosome pair. Despite these findings, knowledge related to the molecular composition of the large heterochromatic band of this W chromosome is restricted to the PcP190 satellite DNA, and no data are available regarding the gene content of either the W or the Z chromosome of Ps. tocantins. Here, we sequenced microdissected Z and W chromosomes of this species to further resolve their molecular composition. Comparative genomic analysis suggests that Ps. tocantins sex chromosomes are likely homologous to chromosomes 4 and 10 of Xenopus tropicalis. Analyses of the repetitive DNA landscape in the Z and W assemblies allowed for the identification of several transposable elements and putative satellite DNA sequences. Finally, some transposable elements from the W assembly were found to be highly diverse and divergent from elements found elsewhere in the genome, suggesting a rapid amplification of these elements on the W chromosome.
Keywords: Anura; Hylidae; microdissection; next generation sequencing; repetitive DNA; sex chromosomes